Low central blood pressure and sympathetic activity predispose for the development of intradialytic hypotension. Issue 14 (9th April 2021) - Wu, Han-Kuei; Chang, Ming-Yang; Cheng, Hao-Min; Hsu, Po-Chi; Lo, Lun-Chien; Chen, Li-Chuan; Lin, Kang-Ping; Chang, Hen-Hong
Abstract : Abstract: Intradialytic hypotension (IDH) may lead to a poor life quality and was associated with cardiovascular mortality in patients under hemodialysis. This study investigated the autonomic nerve and cardiovascular function in the IDH episodes. In this case-control study, 70 end stage renal disease patients (198 visits) were recruited. Pulse wave analysis and heart rate variability were evaluated before hemodialysis. Two definitions of IDH were confirmed by medical records. IDH-f indicated a drop of systolic blood pressure or mean arterial pressure, accompanied with symptoms; IDH-n indicated a low nadir systolic pressure during the hemodialysis. All parameters were evaluated for the possible predisposing factors under each definition. A total of 24 IDH-f and 37 IDH-n were noted in 177 visits. For both definitions, central pulse pressure seemed to be a consistent predisposing factor. Furthermore, lower sympathetic activity (odds ratio [OR] 0.55; 95% confidence interval [CI] 0.35–0.87), lower pulse pressure (OR 0.95; 95% CI 0.92–0.98), and higher augmentation index (OR 17.36; 95% CI 1.48–204.10) were the possible predisposing factors for IDH-f. On the contrary, lower mean arterial pressure (OR 0.87; 95% CI 0.78–0.98) was identified as the possible factor for IDH-n. It was suggested that the lower central pulse pressure and sympathetic activity might be involved in the development of IDH.